A Study on Safety Assessment in A Pipe Concrete Industry - HASHIM BIN HASAN, MOHD ZAHRIN RIZAL BIN HASHIM (Progress in Engineering Application and Technology, 2023)
Pipe manufacturing process is considered as high risk activities as the process involved huge pipe and crane. This study was aimed to identify, assess the hazard and risk involving spun pipe process. In order to achieved the aims, this research objective to be achieved from this study was toidentify hazard and risk related to spun pipe manufacturing process, to analyze identified hazard and risk related to spun pipe manufacturing process and to recommend workable management plans to overcome implementation problems in each work procedure which has been carried out at G-Cast Concrete Production Sdn Bhd. The interview method were used to collect data and the data was analysed using hazard identification, risk assessment and risk control matrix. The tisk was analysed using risk matrix. Out of the 32 hazards found, the risk score indicates that 45% of the hazards have low risk levels, followed by 54% of them that have medium risk levels, and 1% of them that have high hazard levels. A total of 32 hazards were found during the task of producing pipe concrete. These dangers are broken down into safety dangers, which include physical hazard, ergonomic hazard, psychological hazard and chemical hazard. The risk control for high and medium risk identified were recommended to the management.